Mating from a female perspective: Do brown bear females play an active role in mate searching? - Penteriani, Vincenzo; Delgado, María del Mar; Kojola, Ilpo; Heikkinen, Samuli; Fedorca, Ancuta; García‑Sánchez, Pino; Fedorca, Mihai; Find’o, Slavomír; Skuban, Michaela; Balbontín, Javier; Zarzo‑Arias, Alejandra; Falcinelli, Daniele; et al. (BioMed Central, 2025)
Background Limited information exists on the active role of females during mate searching. Theory primarily focuses on male reproductive behaviours, suggesting male distribution follows that of females, while female distribution is influenced by food resources and habitat. This approach might underestimate the females’ role in shaping mating strategies. Incorporating a female perspective into mating studies can enhance our understanding of evolutionary factors. Methods Using GPS data from brown bears Ursus arctos across Finland, Romania and Slovakia, we explored female movement behaviour during the mating period. First, we estimated movement speed, total distance and net distance at a daily scale. Then, we quantitatively described when the movement peaks occur by estimating two critical points of the functions described by each of the aforementioned movement parameters: (1) the point in time when the rate of change in brown bear movement behaviour is the highest; and (2) the point in time when each aspect of brown bear movement is most pronounced. We quantified temporal variations in male and female movements throughout the year using generalized additive mixed models, while we used linear mixed models to assess the relationship between peak movement parameters, bear sex and population. Results Our findings identified two overlooked behaviours: (1) male and female movement parameters showed the highest rate of change during the mating season, challenging the notion of male roaming as the primary mating strategy; and (2) females travelled the longest distances during the mating season, potentially seeking high-quality mates. This behaviour aligns with the strategy of engaging in copulations with multiple males to avoid infanticide. Conclusions Our study reveals novel insights into the active role of female brown bears in mating strategies, challenging traditional male-centric views. These results support the need for detailed investigations into female behaviours across mammalian taxa, which offer potential to advance our understanding of mammalian social and mating systems. Local differences also underscore the importance of social and ecological conditions to explain variation in the female role in mating strategies.
Keywords: females; infanticide; mating excursions; mating strategies; movement ecology; roaming–to–mate; Ursus arctos